Feasibility of preimplantation genetic testing for aneuploidy on frozen-thawed embryos following conventional IVF insemination - Wen, Xiaojun; Li, Zhiming; Cheng, Lizi; Huo, Junye; Yu, Wenjuan; Ou, Zhanhui; Liu, Nengqing; Li, Jieliang; Fang, Xiaowu; Lin, Xiufeng (Frontiers in Endocrinology, 2024)
Objective: Intracytoplasmic sperm injection (ICSI) is commonly employed in preimplantation genetic testing (PGT) to minimize the risk of foreign sperm DNA contamination. Cryopreserved embryos from patients with recurrent miscarriage or repeated implantation failure, who have undergone conventional in vitro fertilization (IVF), can be thawed and biopsied for PGT. Therefore, we aimed to assess the accuracy and effectiveness of preimplantation genetic testing for aneuploidy (PGT-A) on frozen embryos using conventional IVF (c-IVF) insemination methods.Methods: From January 2021 to November 2023, our center conducted 107 thawed cryopreserved embryo biopsy cycles to screen for PGT-A. Among them, 58 cycles used c-IVF insemination, and 49 used ICSI insemination. Basic patient clinical information, laboratory data, PGT test results, and clinical outcome data were collected. To minimize the confounding effects of patient characteristics and embryo quality on PGT-A outcomes, clinical outcomes, and contamination assessment, these variables were included in the analysis. We then evaluated the blastocyst euploidy rate, clinical outcomes, and accuracy of PGT-A results between the two groups and analyzed potential contamination in the c-IVF insemination group.Results: A total of 320 blastocysts underwent PGT-A testing, with 179 blastocysts from c-IVF insemination and 141 from ICSI insemination. Considering participants' baseline characteristics and embryological outcomes, no significant differences were found between the two groups regarding infertility type, average age, body mass index, percentage of PGT-A indications, or quality of embryonic development. Regarding PGT-A results, all 320 biopsy samples were successfully analyzed, showing no statistical variance in chromosomal euploidy, abnormality, or mosaicism rates between the two insemination methods. No parental contamination was detected in the c-IVF insemination group. When assessing clinical outcomes, parameters such as biochemical pregnancy, clinical pregnancy, and miscarriage rates did not exhibit significant discrepancies between the two groups, and no misdiagnoses were reported during the study period.Embryo transfer and PGT-A results are not affected by potential parental contamination in frozen-thawed embryos conceived via c-IVF. PGT-A guided embryo transfer in thawed embryos conceived by c-IVF is a viable and clinically effective approach.